2020
DOI: 10.1017/jmech.2020.38
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Permeation Through A Membrane With Infinitesimal Permeability Under Reynolds Lubrication

Abstract: To understand the lubrication-dominated permeation through a membrane, numerical simulations of permeation through a moving corrugated permeable membrane is carried out with a fully validated numerical method. Through comparisons between the numerical results and the results of an asymptotic analysis of permeate flux (under an infinitesimal permeability condition) using Reynolds lubrication equation, the effect of permeation on lubrication and its inverse effect (i.e., the dependence of permeation on lubricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Using their "consistent direct discretisation" for the DF-IB approach, the no-slip and impermeable conditions on the interface were strictly imposed in a discrete sense, while satisfying the mass and momentum conservations, which enables capturing the sharp distribution of the velocity and pressure at the interface. The DF-IB method was extended to enable permeation of the solvent through the membrane by and Tazaki et al (2020); they showed discretisations that consider the permeable condition for the solvent at the interface. In the present study, we further deal…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using their "consistent direct discretisation" for the DF-IB approach, the no-slip and impermeable conditions on the interface were strictly imposed in a discrete sense, while satisfying the mass and momentum conservations, which enables capturing the sharp distribution of the velocity and pressure at the interface. The DF-IB method was extended to enable permeation of the solvent through the membrane by and Tazaki et al (2020); they showed discretisations that consider the permeable condition for the solvent at the interface. In the present study, we further deal…”
Section: Methodsmentioning
confidence: 99%
“…We further assume an infinitesimal limit for L p to isolate the effect of permeability to develop an asymptotic analytical model. Then, the pressure in Ω 1 is expressed as follows (Takeuchi and Gu 2019;Tazaki et al 2020):…”
Section: Analytical Models Of Lubrication-induced Permeate Fluxesmentioning
confidence: 99%
“…Equations ( 2)-( 4) are numerically solved on a rectangular mesh (i.e., nonconforming to the membrane geometry) by the discrete-forcing immersed-boundary (DF-IB) method provided in Refs. [4,16,17]. To simulate fluid permeation on a rectangular mesh, reproducing the sharpness of the pressure discontinuity across the membrane is critical [18,19].…”
Section: Problem Statementmentioning
confidence: 99%
“…[20,21] was developed to reproduce the sharpness in the pressure distribution at a solid surface by handling the mass and momentum conservations even in the immediate vicinity of the solid surface. The present method [4,16,17] solves the problem of permeation by incorporating the pressure discontinuity term into the pressure Poisson equation of the DF-IB method. A brief summary of the numerical method is provided in the Supplemental Material [22].…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation